2011
DOI: 10.1093/rheumatology/ker018
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of repeated treatment with B-cell depletion therapy in systemic lupus erythematosus: an evaluation

Abstract: Repeated cycles of BCDT with rituximab are effective in treating refractory SLE and has a favourable safety profile. Retreatment may produce a more sustained clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 17 publications
2
33
0
1
Order By: Relevance
“…Seventy-six of these articles had to be further excluded, as these provided incomplete data or had irrelevant objectives and were unsuitable for meta-analysis. Remaining 31 articles were included for meta-analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Flowchart of the studies evaluated is represented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Seventy-six of these articles had to be further excluded, as these provided incomplete data or had irrelevant objectives and were unsuitable for meta-analysis. Remaining 31 articles were included for meta-analysis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Flowchart of the studies evaluated is represented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Percentages of patients in each group were similar (7 of 12 [58%] in the low IgM group and 22 of 45 [49%] in the normal IgM group). Detailed patient demographics and clinical responses of this cohort of 57 patients have been previously described 31, 32, 33. The median age at the time of the first rituximab treatment cycle was 34 years (range 17–74 years).…”
Section: Resultsmentioning
confidence: 99%
“…Tables 1 and 2 show a summary of included studies. We found 2 RCTs (Furie et al, 2009;Merrill et al, 2011) and 19 observational studies (Leandro et al, 2002;Leandro et al, 2005;Vigna-Perez et al, 2006;Gunnarsson et al, 2007;Tokunaga et al, 2007;Sutter et al, 2008;Tamimoto et al, 2008;Melander et al, 2009;Pepper et al, 2009;Catapano et al, 2010;Lateef et al, 2010;Ramos-Casals et al, 2010;Terrier et al, 2010;Pinto et al, 2011;Roccatello, 2011;Tony et al, 2011;Turner-Stokes et al, 2011;Vital et al, 2011;Arce-Salinas et al, 2012).…”
Section: Resultsmentioning
confidence: 78%
“…Although studies 11 (Turner-Stokes et al, 2011), 12 (Roccatello et al, 2011), and 14 (Catapano et al, 2010) also reported on BILAG, they were excluded due to missing data. The homogeneity χ 2 test value of BILAG data from studies 1, 2, 9, and 10 was 3.95 (P=0.27 (>0.05)); therefore, the 4 studies were considered homogeneous.…”
Section: Effect On Bilagmentioning
confidence: 99%